Dinamika Kebijakan Moneter dan Diplomasi Ekonomi dalam Menjaga Stabilitas Nilai Tukar: Studi Kasus Indonesia di Pasar Internasional - Siti Mardiyani; Jihan Nabila; Andri Kurniawan; Ari Elfrian; Zakya Maulani; Mike Apriyanti; Joel Ferdinand Sinaga (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study examines the dynamics of monetary policy and economic diplomacy in maintaining the stability of the Rupiah exchange rate in the context of Indonesia’s international financial market. Indonesia’s economic stability is closely tied to the Rupiah’s value, which is influenced by both domestic economic policies and external global factors. The study analyzes the effectiveness of various monetary policy instruments used by Bank Indonesia, such as the benchmark interest rate, foreign exchange market interventions, open market operations, and minimum reserve requirements. Furthermore, it explores the role of economic diplomacy, including bilateral swap agreements and international cooperation, in enhancing Indonesia's foreign exchange reserves and stabilizing the Rupiah. Despite these efforts, external challenges such as global economic uncertainty, commodity price volatility, and geopolitical tensions continue to pose risks to exchange rate stability. The study concludes with strategic recommendations for strengthening monetary policy, including diversification of foreign exchange revenue, enhancing domestic financial markets, and fostering synergy between fiscal and monetary policies.